2002
DOI: 10.1113/jphysiol.2001.012721
|View full text |Cite
|
Sign up to set email alerts
|

D1 and D2 receptor‐mediated dopaminergic modulation of visual responses in cat dorsal lateral geniculate nucleus

Abstract: The mean tonic activity of five X-and five Y-cells is plotted over time after onset of QUIN application with 10-20 nA. The curves were slightly smoothed by calculating sliding means from three successive responses. The responses were normalized to the mean of the three first response levels, which were set to 0 on the graph. Continuous lines show Y-cell activity, dashed lines that for the X-cells. The grey lines show overall means for X-and Y-cells. Regression lines have also been added.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…Moreover, D 2 -like dopamine receptor binding sites have been shown in the human thalamus using in vivo radioligands, with a distribution that resembles that of the dopamine innervation described here (Rieck et al, 2004). Finally, dopamine and D 1 -like and D 2 -like dopamine receptor agonists modulate visual responses of the cat dorsal lateral geniculate thalamic nucleus (Zhao et al, 2001(Zhao et al, , 2002). …”
Section: Discussionmentioning
confidence: 78%
“…Moreover, D 2 -like dopamine receptor binding sites have been shown in the human thalamus using in vivo radioligands, with a distribution that resembles that of the dopamine innervation described here (Rieck et al, 2004). Finally, dopamine and D 1 -like and D 2 -like dopamine receptor agonists modulate visual responses of the cat dorsal lateral geniculate thalamic nucleus (Zhao et al, 2001(Zhao et al, , 2002). …”
Section: Discussionmentioning
confidence: 78%
“…This implies that conversely, depletion of these neuromodulators may lead to slow synchronous rhythms in the LGN. More recently, Zhao et al (2002) have shown that dopaminergic neuro-receptors affect information transmission efficiency in the LGN by neuromodulation of the IN cells. Furthermore, their study suggest a stronger suppression of the TCR cells with blockage of GABA A neuro-receptors.…”
Section: Resultsmentioning
confidence: 99%
“…This condition simulates the blocking of GABA-ergic feed-forward inhibition of the TCR due to neuromodulatory effects on the IN by several neurotransmitters such as acetylcholine (McCormick, 1992) and dopamine (Zhao et al, 2002). The time series output of both TCR and TRN in Figure 4A shows a distinct bifurcation with synchronized waxing-and-waning of amplitude within the alpha band frequency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of dopamine in the regulation of sleep-related activity in the thalamus is unclear. It was suggested, that dopamine acts by indirectly inhibiting relay cell activity through the excitation of local interneurons [3,196]. Indeed, dopamine modulates the inhibitory synaptic transmission to dLGN TC neurons by activation of D 2 -like receptors on local GABAergic interneurons [123].…”
Section: Thalamic Interneurons and Dopaminementioning
confidence: 99%